Radiosynthesis and validation of [18F]fluoroestradiol in a Synthra plus research platform for use in routine clinical practice. (5th September 2022) - Pereira, María Pía; Tejería, María Emilia; Zeni, Maia; Gambini, Juan Pablo; Duarte, Pablo; Rey, Ana; Giglio, Javier
Abstract : In this practitioner protocol, the optimization of the radiochemical synthesis of [ 18 F]fluoroestradiol (FES) on the Synthra RNplus research automated platform is described in detail and a quality control (QC) summary of three validation productions is presented. In comparison with published synthesis methods developed on other platforms, the yield was considerably improved (40%–45% ndc). The other important improvement is the reduction of the required concentration of H2 SO4 avoiding the production of high concentrations of acidic vapors that can deteriorate the module. Purification was achieved by solid phase extraction, and the required adaptation of an external heating plate to the module to evaporate the ethanol is also described. The product was obtained with high radiochemical purity and fulfilled all the requirements of current Good Manufacturing Practice (cGMP). The final product is formulated as a sterile, pyrogen‐free solution suitable for human injection. To the best of our knowledge, this is the first report of FES production using this type of module.